Monetary target announcements, reputation and hysteresis - Hans Peter Grüner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
Two signaling games of monetary policy are considered: game one examines the effect of hysteresis on the labor market on the results of the repeated monetary policy game. Disciplinary effects of reputation disappear in presence of hysteresis. The second game compares weifare effects of monetary target announcements to those of a rigid rule under alternative assumptions on the policymaker's type space.
Keywords: C73; E52; E58; 330; Signaling Games; Monetary Policy; Credibility; Reputation; Hysteresis; Geldpolitik; Glaubwürdigkeit; Arbeitsmarkt; Hysteresis; Theorie